Measurement of Physical Fitness Employees Solo Net Surakarta - Baskoro Nugroho Putro; Djoko Nugroho; Budhi Satyawan; Sunardi; Waluyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Physical fitness is an essential aspect of life. The role of physical fitness in living life is limited to athletes and society in general. For workers, having a fit body will increase productivity because they do not feel tired quickly. Good physical fitness is supported by good endurance as well. However, endurance does not play a single role in supporting physical activity. Having good endurance is indeed beneficial and is a must for individuals involved in activities or work that take a long time. Please note that every activity or work has specific targets that must be completed. Other aspects must be possessed in order to become an individual with complete physical fitness. The demands of the quality of physical fitness in the general public certainly cannot be equated with athletes' standards. For the general public, not getting tired of doing work and meeting the targets given by the institution where they work is already extraordinary.